DOP018 Baseline ILC1 distribution in blood predicts response to ustekinumab in patients with refractory Crohn's disease. (16th January 2018) - Creyns, B; Verstockt, B; Cremer, J; Ferrante, M; Vermeire, S; Jan, C; Van Assche, G; Breynaert, C
Abstract: Background: Innate lymphoid cells (ILCs) are recently identified immune cells with a high cytokine producing capacity at mucosal barriers. In patients with active Crohn's disease (CD), a shift in is observed from homeostatic ILC3s towards pro-inflammatory ILC1s in the intestines. Ustekinumab (UST), targeting the IL-12/23 shared p40 subunit, was recently approved by FDA and EMA for treatment of moderate-to-severe CD. As IL-12 and IL-23 play distinct roles in the plasticity of ILC1 and ILC3s, we studied the effect of ustekinumab on ILC populations in blood. Methods: We included 46 CD patients (68% female, median age 42) refractory to anti-TNF therapy and vedolizumab with a median Simplified Endoscopic Score (SES-CD) of 16.5, initiating UST (6 mg/kg IV at induction, followed by subcutaneous UST 90 mg q8w thereafter). Blood samples were prospectively collected before start and at 4, 8 and 24 weeks. Endoscopic response was assessed at week 24, and defined as a −50% SES-CD decrease. ILCs were studied in isolated flow cytometry. Results: Patients with ( n = 6) and without ( n = 40) endoscopic response at week 24 had a similar inflammatory burden, reflected by similar median faecal calprotectin (1800 vs. 1225 µg/g, p = 0.44) and C-reactive protein (23.9 vs. 10.3 mg/l, p = 0.10) levels at baseline. Though, baseline endoscopic activity was much higher in patients responding to UST, compared with non-responders (median SES-CD 22 vs. 14, p = 0.02). Baseline contribution of ILC1s in the total ILC pool was significantly lower in responders compared with non-responders before start of therapy (7.39% vs. 16.90%, p = 0.017) (Figure 1A). In contrast, ILC2s were elevated in responders as compared with non-responders at baseline (70.1% vs. 40.8%, p = 0.02) (Figure 1B). There was no significant difference in NCR- ILC3s ( p = 0.12). After week 4 treatment a significant increase in NCR- ILC3 frequency was observed as compared with baseline independent of response ( p < 0.001). This trend persisted at 8 weeks ( p = 0.02) but could no longer be observed after 24 weeks ( p = 0.19). Conclusions: This study is the first to show how biological therapy impacts ILC populations in peripheral blood. Increased levels of ILC1s in peripheral blood at baseline may be a predictive biomarker for non-response to UST. Non-response may be explained by an increased reservoir of pro-inflammatory ILC1s in the circulation which can migrate towards the gut to annihilate treatment effects. Validation is needed in a larger and independent cohort with inclusion of biopsies. Overall these findings may guide individualised selection of biological agents in Crohn's disease, and provide mechanisms of primary (non-)response to UST.